Pengaruh Beberapa Bahan Aktif dalam Formulasi Rodentisida terhadap Metabolisme dan Perilaku Tikus Putih (Rattus norvegicus Wistar) di Laboratorium - Wahyu Daradjat Natawigena; Ichsan Nurul Nurul Bari; Chindera Rindhany Surachman (Gunung Djati Conference Series, 2021)
The existence of rats often causes losses in various areas of human life, such as in agriculture, plantations, and communities. Chemical rat control is effective both indoors and outdoors, with toxic baits such as rodenticides. However, rodenticides are considered ineffective by the community and pest control services. This experiment aimed to obtain the differences in metabolism and behavior of rats due to consuming rodenticides with several types of active ingredients. The experiment was carried out from January 2020 to March 2020 at the Plant Pest Laboratory, Vertebrate Division, Department of Plant Pests, Faculty of Agriculture, Padjadjaran University. The study used a randomized block design (RBD) experimental method with 5 treatments, there were treatments without active ingredients (control), Coumatetralyl, Brodifacoum, Bromadiolone, and Warfarin rodenticide, with 6 replications. The parameters tested were rat metabolisms i.e., changes in body weight, feed and drinking consumption, feces and urine production, and rat behavior. The results showed that there were differences in metabolic effects and rat behavior due to consuming rodenticides with Coumatetralyl, Brodifacoum, Bromadiolone, and Warfarin. Four active ingredients affected decreasing body weight, feed and drink consumption, as well as the production of feces and urine, but Coumatetralyl rodenticide causes an increased drink consumption and urine production on the first day. The effect of four active ingredients in the rodenticide formulation has almost the same symptoms, and has a mechanism as an anticoagulant and an inhibitor of the central nervous system. The differences in rats behavior lie in the timing of symptoms of poisoning.